Membangun Kepuasan Karir Dengan Kecerdasan Emosional Dan Perilaku Inovatif: Moderasi Efikasi Diri - noerchoidah, noerchoidah -; Nurdina, Nurdina (Jurnal Manajerial, 2024)
Background – Observing the practical conditions at the bank, frontline employees are the main gateway for the company to serve customers. Frontline employees as an indicator of success in customer service. Employees in the service department often experience stress when dealing with many customers with various problems and characters. Therefore, emotional intelligence and innovative behavior are needed in providing services in dealing with customers in different ways. Innovative behavior can encourage career satisfaction for private bank employees in Surabaya. Objectives – This research examines the moderating influence of emotional intelligence, innovative behavior, career satisfaction, and self-efficacy. Design/ Method/ Approach - The research method uses a quantitative explanatory research design. Questionnaires are used to collect data either directly from respondents or through the Google form. Purposive sampling technique was used to take samples from 156 private bank employees in Surabaya. The collected data were analyzed using SEM-PLS. Results and Discussion – The research results show that emotional intelligence has a positive and significant effect on innovative behavior. Innovative behavior has a positive and significant effect on employee career satisfaction, Emotional intelligence has a positive and significant effect on career satisfaction, Innovative behavior mediates between emotional intelligence and career satisfaction, Self-efficacy moderates between emotional intelligence and innovative behavior, Self-efficacy moderates between emotional intelligence and employee career satisfaction private bank in Surabaya. Conclusion – Emotional intelligence can increase innovative behavior and career satisfaction. Innovative behavior can mediate emotional intelligence and career satisfaction. Self-efficacy can moderate between emotional intelligence on innovative behavior and emotional intelligence on career satisfaction. Research Implications – This study provides recommendations to private bank leaders in Surabaya to pay attention to managing and motivating emotional intelligence, innovative behavior, self-efficacy, and employee career satisfaction to improve performance. Research Limitations - The research sample was only private bank employees in the Surabaya area. Comparative research can be conducted on government bank employees to compare findings. This research was carried out in a cross section manner where only observations were made at the time of the research, preferably requiring longitudinal research.